Model BERTAUT: Solusi Inovatif untuk Meningkatkan Aktivitas dan Keterampilan Kerja Sama Peserta Didik Sekolah Dasar - Oktavia, Khalida; Aslamiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main issues at SDN Palimbang Gusti 1 involved low student participation, poor collaboration skills, and unsatisfactory learning outcomes in the subject of Pancasila Education for Grade V. To address these challenges, the BERTAUT learning model was implemented. This study aimed to examine the effectiveness of the BERTAUT model in improving teacher activity, student participation, collaboration skills, and learning outcomes. The research used a Classroom Action Research (CAR) approach, involving 8 Grade V students (3 boys and 5 girls) during the second semester of the 2024/2025 academic year. Qualitative data were collected through observations of teacher activity, student engagement, and collaboration, while quantitative data were obtained from learning outcomes and classical mastery. The results showed improvement across all areas. In the fourth meeting, teacher activity reached 94% (categorized as "very good"), student participation reached 87% ("very active"), collaboration skills achieved 100% ("very skilled"), and learning outcomes also showed 100% mastery. These findings indicate that the implementation of the BERTAUT model successfully enhanced the overall quality of the learning process